Constitutive flow behavior and microstructural evolution of 17 vol% SiCp/7055Al composite during compression at elevated temperature - Binbin Tang; Haitao Wang; Peipeng Jin; Xianquan Jiang (Journal of Materials Research and Technology, 2020)
A study is conducted on the flow stress behavior of the spray-deposition processed 17 vol% SiCp/7055Al composite through hot compression tests at the temperatures ranging from 250 °C to 450 °C and the strain rates of 0.001–1 s−1, including microstructure evolution. As indicated by the calculation results, the deformation activation energy for the SiCp/7055Al composite is 145.28 kJ/mol. All of the obtained flow curves are characterized by dynamic recovery and/or dynamic recrystallization. The hot deformation of the composites in the temperature range of 250–350 °C and strain rate region of 1–0.001 s−1 exhibited the typical characteristics of dynamic recovery. As the deformation temperature increases, the deformation mechanism of the composites shifted to dynamic recrystallization over time. The flow stress showed a decreasing trend with the increase of deformation temperature and the decrease of strain rate, as reflected by a Zener–Hollomon parameter in hyperbolic sine equation. According to the processing map, the optimum hot workability domain is the peak region located around 430–450 °C and 0.001–0.03 s−1. In addition, the orientation distribution function ODFs were calculated according to the pole figures, which revealed that the textures of the composites are significantly different at the varied hot deformation parameters.